2022
DOI: 10.1186/s40359-022-00717-8
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and grief in young adults after the loss of a close friend: a qualitative study

Abstract: Background Although many lose a close friend each year, they are seldom the focus of grief research. However, these losses often cause severe and long-lasting reactions. Deaths among adolescents and young adults are also often caused by traumatic events, e.g. from accidents, suicides, and homicides, placing them at significant risk for complicated grief reactions. The focus of this paper is bereaved friends after the shootings at Utøya, Norway in 2011, which is among a few studies that focus on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Losing someone you love is a painful experience, usually followed by grief and emotional distress 1 . After traumatic losses, it is common to engage with death and to also experience feelings of disbelief, anger, shock, guilt, depression, loneliness, sleep difficulties, emptiness, hopelessness, or vulnerability 2 . Most bereaved individuals cope with the loss over time and return to a compatible level of functioning 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Losing someone you love is a painful experience, usually followed by grief and emotional distress 1 . After traumatic losses, it is common to engage with death and to also experience feelings of disbelief, anger, shock, guilt, depression, loneliness, sleep difficulties, emptiness, hopelessness, or vulnerability 2 . Most bereaved individuals cope with the loss over time and return to a compatible level of functioning 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 After traumatic losses, it is common to engage with death and to also experience feelings of disbelief, anger, shock, guilt, depression, loneliness, sleep difficulties, emptiness, hopelessness, or vulnerability. 2 Most bereaved individuals cope with the loss over time and return to a compatible level of functioning. 3 Common strategies used for coping include positive reframing, planning and seeking social support, active coping, emotional and instrumental support, acceptance of death, religion, and humor.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of psychosocial help to the bereaved after the 2011 terror attack in Norway where 77 people died, 25% of a sample of 67 bereaved reported rigidity in the professional services regarding who should and should not receive help ( Dyregrov et al, 2015 ). Another study, based on interviews of bereaved friends after this attack, reported common experiences of not getting help or being acknowledged as bereaved ( Johnsen & Tømmeraas, 2022 ). Thus, the experience of differing recognition of needs and access to help depending on relation to the deceased is a shared experience both for DRD-bereaved and other traumatically bereaved people.…”
Section: Discussionmentioning
confidence: 99%